Antimicrobial and host cell-directed activities of Gly/Ser-rich peptides from salmonid cathelicidins. (December 2016) - D'Este, Francesca; Benincasa, Monica; Cannone, Giuseppe; Furlan, Michela; Scarsini, Michele; Volpatti, Donatella; Gennaro, Renato; Tossi, Alessandro; Skerlavaj, Barbara; Scocchi, Marco
Abstract: Cathelicidins, a major family of vertebrate antimicrobial peptides (AMPs), have a recognized role in the first line of defense against infections. They have been identified in several salmonid species, where the putative mature peptides are unusually long and rich in serine and glycine residues, often arranged in short multiple repeats (RLGGGS/RPGGGS) intercalated by hydrophobic motifs. Fragments of 24–40 residues, spanning specific motifs and conserved sequences in grayling or brown, rainbow and brook trout, were chemically synthesized and examined for antimicrobial activity against relevant Gram-positive and Gram-negative salmonid pathogens, as well as laboratory reference strains. They were not active in complete medium, but showed varying potency and activity spectra in diluted media. Bacterial membrane permeabilization also occurred only under these conditions and was indicated by rapid propidium iodide uptake in peptide-treated bacteria. However, circular dichroism analyses indicated that they did not significantly adopt ordered conformations in membrane-like environments. The peptides were not hemolytic or cytotoxic to trout cells, including freshly purified head kidney leukocytes (HKL) and the fibroblastic RTG-2 cell line. Notably, when exposed to them, HKL showed increased metabolic activity, while a growth-promoting effect was observed on RTG-2 cells, suggesting a functional interaction of salmonid cathelicidins with host cells similar to that shown by mammalian ones. The three most active peptides produced a dose-dependent increase in phagocytic uptake by HKL simultaneously stimulated with bacterial particles. The peptide STF(1–37), selected for further analyses, also enhanced phagocytic uptake in the presence of autologous serum, and increased intracellular killing of live E. coli . Furthermore, when tested on HKL in combination with the immunostimulant β-glucan, it synergistically potentiated both phagocytic uptake and the respiratory burst response, activities that play a key role in fish immunity. Collectively, these data point to a role of salmonid cathelicidins as modulators of fish microbicidal mechanisms beyond a salt-sensitive antimicrobial activity, and encourage further studies also in view of potential applications in aquaculture. Highlights: Salmonid cathelicidin-derived peptides show medium-sensitive antimicrobial activity. They are not cytotoxic to fish cells and promote proliferation of trout fibroblasts. Peptide STF (1–37) potentiates phagocytosis and respiratory burst in trout leukocytes. STF (1–37) and β-glucan act synergistically to immunostimulate trout leukocytes.